2006
DOI: 10.1007/s10562-005-9193-4
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Properties of Ni3Al Foils for Methanol Decomposition

Abstract: Hydrogen was produced by methanol decomposition over cold-rolled foils of intermetallic compound Ni 3 Al which is known as an excellent high-temperature structural material. We found high catalytic activity and selectivity for methanol decomposition in flat cold-rolled Ni 3 Al foils. The catalytic activity was enhanced above 713 K by the spontaneous formation of fine Ni particles dispersed on carbon nanofibers during the reaction, resulting in high catalytic performance. The results demonstrate that the Ni 3 A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 25 publications
3
48
1
Order By: Relevance
“…An increase in the water content in the mixture improves the conversion. Small amounts of water (~5%) result in a small improvement in the methanol decomposition -the process begins earlier and reaches a level of 98% at temperatures above 430 O C. This is in contrast to the recent literature, where a comparable level of conversion (98%) [5,6] was obtained at a higher temperature -about 520 O C -for 29 hours. At temperatures similar to those used in our experiment (about 440 O C), the authors of the above-cited literature obtained less than 80% methanol conversion for 65 hours.…”
Section: Methodscontrasting
confidence: 69%
See 4 more Smart Citations
“…An increase in the water content in the mixture improves the conversion. Small amounts of water (~5%) result in a small improvement in the methanol decomposition -the process begins earlier and reaches a level of 98% at temperatures above 430 O C. This is in contrast to the recent literature, where a comparable level of conversion (98%) [5,6] was obtained at a higher temperature -about 520 O C -for 29 hours. At temperatures similar to those used in our experiment (about 440 O C), the authors of the above-cited literature obtained less than 80% methanol conversion for 65 hours.…”
Section: Methodscontrasting
confidence: 69%
“…Another method for obtaining thin foils (with microcrystalline structures only) was reported by Hirano et al [4], where directionally solidified ingots were rolled at room temperature. For materials obtained according to this method, the authors confirmed good catalytic properties in methanol decomposition [5,6].…”
Section: Introductionmentioning
confidence: 61%
See 3 more Smart Citations